Changing global policy to deliver safe, equitable, and affordable care for women's cancers - Ginsburg, Ophira M.; Badwe, Rajendra A.; Peter A. Boyle, Peter; Derricks, Gemma; Dare, Anna J.; Evans, Timothy Grant; Eniu, Alexandru E.; Jiménez, Jorge C.Moreno; Kutluk, Tezer M.; De Lima Lopes, Gilberto L.; Mohammed, Sulma Ibrahim; Qiao, Youlin; et al. (© 2017 Lancet Publishing Group, 2018)
This review was published in The Lancet [© 2017 Elsevier Ltd] and the definitive version is available at: http://doi.org/10.1016/S0140-6736(16)31393-9 The Journal's website is at: https://www.sciencedirect.com/science/article/pii/S0140673616313939?via%3Dihub